Insulin-loaded polymeric mucoadhesive nanoparticles: development, characterization and cytotoxicity evaluation (Brazilian Journal of Pharmaceutical Sciences, 2018)
Mucoadhesive nanoparticles are particularly interesting for delivery through nasal or pulmonary routes, as an approach to overcome the mucociliary clearance. Moreover, these nanoparticles are attractive for peptide and protein delivery, particularly for insulin to treat diabetes, as an alternative to conventional parenteral administration. Thus, chitosan, a cationic mucoadhesive polysaccharide found in shells of crustaceans, and the negatively-charged dextran sulfate are able to form nanoparticles through ionic condensation, representing a potential insulin carrier. Herein, chitosan/dextran sulfate nanoparticles at various ratios were prepared for insulin loading. Formulations were characterized for particle size, zeta potential, encapsulation efficiency, scanning electron microscopy, differential scanning calorimetry, and in vitro drug release. Moreover, the interaction with mucin and the cytotoxicity against a lung cell line were studied, which altogether have not been addressed before. Results evidenced that a proper selection of polyelectrolytes is necessary for smaller particle size formation and also the composition and zeta potential impact encapsulation efficiency, which is benefited by the positive charge of chitosan. Insulin remained stable after encapsulation as evidenced by calorimetric assays, and was released in a sustained manner in the first 10 h. Positively-charged nanoparticles based on chitosan/dextran-sulfate at the ratio of 6:4 successfully interacted with mucin, which is a prerequisite for delivery to mucus-containing tissues. Finally, insulin-loaded nanoparticles displayed no cytotoxicity effect against lung cells at tested concentrations, suggesting the potential for further in vivo studies.